Korelasi Antara Gaya Belajar dan Kemandirian Belajar Dengan Hasil Belajar Siswa Pada Pembelajaran Tematik Kelas V SDN 13 Pontianak Barat - Heny Rahayu; Siti Halidjah; Rio Pranata (Journal on Education, 2023)
This study aims to describe the correlation between learning styles and learning independence with student learning outcomes in thematic learning class VB SD Negeri 13 Pontianak Barat. The method used in this research is descriptive in the form of a correlation study. The population of this study were all VB class students at SD Negeri 13 Pontianak Barat, totaling 32 students. Sampling was carried out using purposive sampling with a sample of 32 students in VA class at SD Negeri 13 Pontianak Barat. Data collection techniques use indirect communication to collect data on learning styles, learning independence and documentary study techniques for learning outcomes. The collection tool is a questionnaire. Data analysis technique uses Product moment. The correlation between learning styles and learning outcomes is 0.160, between learning independence and learning outcomes is 0.122, and between learning styles and learning independence with learning outcomes is 0.184, in the very low category. rtable of 0.349 with a significance level of 5%, then 0.184> 0.349. So it can be concluded that Ho is accepted and Ha is rejected because there is no correlation between learning styles and learning independence with student learning outcomes in class VB SD Negeri 13 Pontianak Barat.